PALEOETHNOLOGY AND THE CURATOR OF THE ETHNOGRAPHIC DEPARTMENT OF THE RUSSIAN MUSEUM A. MILLER - V. A. Dmitriev (Гуманитарные и юридические исследования)
Paleoethnology was a discipline to hold certain temporary position in the history of archeology and ethnography. In Russia it prospered in the 1920s, which was mainly due to the development of world science in the preceding period. In the implementation of the principles of paleoethnology a significant role belonged to museum organizations, in particular the Ethnographic department of the Russian Museum in St. Petersburg - Leningrad (EDRM). Alexander Miller (1875-1935), a prominent representative of national trends of paleoethnology, largely determined the principles of EDRM work up to the 1930's. A. Miller developed methods of field work, combined ethnographic and archaeological research incorporating archaic search in folk culture.